2015
DOI: 10.1007/s11665-015-1646-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen on Passivity of Nickel-Free Stainless Steels by Electrochemical Impedance Spectroscopy Analysis

Abstract: The effects of different nitrogen contents on the passivity of nickel-free stainless steels in 0.5 M sulfuric acid + 0.5 M sodium chloride solution were investigated by electrochemical impedance spectroscopy in the potential ranges of active dissolution and active-passive transition. A simplified reaction model containing adsorbed intermediates involved dissolution process, and passivation process was proposed to explain the impedance characteristics. Based on both equivalent circuit and mathematical model ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…At a higher N content, the R p value was larger, indicating a higher protective ability of passive film and a lower corrosion rate 55 . It is in accordance with the results conducted by Wu et al 56 that the addition of N improved the stability of passive film and thus enhanced the passivation of austenitic steel.…”
Section: Electrochemical Testssupporting
confidence: 93%
“…At a higher N content, the R p value was larger, indicating a higher protective ability of passive film and a lower corrosion rate 55 . It is in accordance with the results conducted by Wu et al 56 that the addition of N improved the stability of passive film and thus enhanced the passivation of austenitic steel.…”
Section: Electrochemical Testssupporting
confidence: 93%
“…At a higher nitrogen content, the R p value was larger, indicating a higher protective ability of passive film and a lower corrosion rate [49]. It is in accordance with the results conducted by Wu [50] et al that the addition of N improved the stability of passive film and thus enhanced passivation of austenite steel.…”
Section: E / V(vs Sce) I / (A•cmsupporting
confidence: 89%
“…In the passivated film obtained in the tested solution, the signals corresponding to the Cr 2p3/2 spectra show that there exist three constituent peaks representing metallic state of (Cr 0 ), Cr(OH) 3 /CrOOH, and Cr 2 O 3 [8,14,[36][37][38]. Similar structures of (Cr(OH) 3 + Cr 2 O 3 ) can be observed in the films formed on stainless steel in the strong (pH 0.8) and weak (pH 5) acid solutions [17].…”
Section: Xps Resultsmentioning
confidence: 99%
“…It has been reported that the addition of nitrogen could drastically increase both the yield strength and ultimate tensile strength without sacrificing the ductility and toughness [2][3][4][5][6]. Moreover, the addition of nitrogen could also improve the corrosion, corrosion fatigue, and stress corrosion cracking resistance of stainless steels [5,[7][8][9][10][11][12][13]. Therefore, nitrogen is a strong austenite stabilizing element and is expected to substitute for relatively expensive element of nickel to make HNSS a resource-saving materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation